Phagocytosis and Killing of Bacteria by Professional Phagocytes and Dendritic Cells - Nagl, Markus (American Society for Microbiology, 2002)
Dendritic cells (DC) represent a class of professional antigen-presenting cells whose primary function is to alert the immune system, not to clear invading microorganisms. The objective of our study was to compare the abilities of polymorphonuclear neutrophilic leukocytes (PMN), monocytes, monocyte-derived macrophages (MDM), monocyte-derived immature DC (imDC), and mature DC (maDC) to ingest and destroy Staphylococcus aureus and Escherichia coli. Acridine orange staining and fluorescence microscopy demonstrated that MDM, followed by monocytes, imDC, and PMN, internalized bacteria well but that maDC exhibited less pronounced phagocytic activity. PMN, monocytes, and MDM exhibited a much higher capacity to kill ingested bacteria than both imDC and maDC. In summary, these data are in agreement with the generally accepted idea that different types of leukocytes fulfill specialized tasks in antigen presentation and killing of pathogens.